The Potential of Systematization of the Theories of Education for Solving of Contradictions of Ukrainian Higher Education Development - Bazaluk, Oleg; Fatkhutdinov, Vasyl; Svyrydenko, Denys (Studia Warmińskie, 2018)
The article presents a historical and philosophical analysis of ideas that influenced the development of educational theories. After this analysis, educational theories were systematized. The authors concluded that the general theory of education can be reduced to two directions of development, for which the ideas of Plato and Socrates are foundations. The Platonic theory of education, as well as those derived from its source, seek answers to the question: How should the young generation be shaped and educated in the education process and how can the state influence the orientation of this education? In turn, the socratic theories of education are of an egalitarian character and focus on the ways of education. The authors of the conclusions emphasized that the undertaken analyzes, and especially the systematization of the theory of education based on the reference to two models, Plato and Socrates, can be an inspiration in finding ways to overcome the deference in the Ukrainian system of higher education.